Pengaruh Budaya Organisasi dan Motivasi Terhadap Kinerja Karyawan Melalui Semangat Kerja Sebagai Variabel Intervening Pada PT Wilmar Nabati Teluk Bayur Padang - Putri, Suci Zirana; Sari, Marta Widian; Sari, Yosi Puspita (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine the influence of organizational culture and motivation on employee performance, with work morale as an intervening variable, among employees at PT Wilmar Nabati Teluk Bayur Padang. Data collection methods included surveys and questionnaires, with up to 80 respondents. Path analysis using the SmartPLS application was used for analysis. The results obtained from partial tests revealed a significant effect of organizational culture on work morale. Motivation significantly influences job satisfaction and work morale. Organizational culture significantly influences employee performance. Motivation also insignificantly influences employee performance. Work morale significantly influences employee performance. Organizational culture significantly influences employee performance through work morale as an intervening variable. Motivation significantly influences employee performance through work morale as an intervening variable.